2022
DOI: 10.1038/s41590-022-01289-w
|View full text |Cite
|
Sign up to set email alerts
|

Differences in CD80 and CD86 transendocytosis reveal CD86 as a key target for CTLA-4 immune regulation

Abstract: CD28 and CTLA-4 (CD152) play essential roles in regulating T cell immunity, balancing the activation and inhibition of T cell responses, respectively. Although both receptors share the same ligands, CD80 and CD86, the specific requirement for two distinct ligands remains obscure. In the present study, we demonstrate that, although CTLA-4 targets both CD80 and CD86 for destruction via transendocytosis, this process results in separate fates for CTLA-4 itself. In the presence of CD80, CTLA-4 remained ligand boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 53 publications
0
71
0
Order By: Relevance
“…As expected, greater detection of CD80 uptake was observed compared to CD86 due to the higher affinity of CTLA-4 for CD80. In addition, we have observed a faster degradation of CD86, which also contributes to its more limited detection ( 37 ). Together, these data demonstrated that the universal gene editing approach could restore CTLA-4 expression and function in patient-derived T cells with three different heterozygous mutations in CTLA-4.…”
Section: Resultsmentioning
confidence: 87%
“…As expected, greater detection of CD80 uptake was observed compared to CD86 due to the higher affinity of CTLA-4 for CD80. In addition, we have observed a faster degradation of CD86, which also contributes to its more limited detection ( 37 ). Together, these data demonstrated that the universal gene editing approach could restore CTLA-4 expression and function in patient-derived T cells with three different heterozygous mutations in CTLA-4.…”
Section: Resultsmentioning
confidence: 87%
“…CD80 remain bound to CTLA-4 after transendocytosis, accompanied by the ubiquitylation of CTLA-4 and its trafficking toward late endosomes and lysosomes. In contrast, CD86 readily dissociates after internalization, which leaves CTLA-4 unmodified and permits its recycling for further ligand capture . Therefore, CD80 may be more critical to antigen presentation than CD86 because it promotes the shutdown and degradation of the immunosuppressive signaling molecule CTLA-4.…”
Section: Resultsmentioning
confidence: 99%
“…after internalization, which leaves CTLA-4 unmodified and permits its recycling for further ligand capture. 23 Therefore, CD80 may be more critical to antigen presentation than CD86 because it promotes the shutdown and degradation of the immunosuppressive signaling molecule CTLA-4.…”
Section: Resultsmentioning
confidence: 99%
“…The PD-1/PD-L1 pathway can form a local immunosuppressive environment [ 60 ] and play an important role in gastric cancer cell immune escape [ 61 ]. CTLA-4 mediates immunosuppression by indirectly reducing signaling through the costimulatory receptor CD28 [ 62 ]. Our results found that MAGEA11 is negatively correlated with PD-L1, PD-1, and CTLA-4, and it may be that anti-PD-1/PD-L1 has poor efficacy in the high expression group of MAGEA11 .…”
Section: Discussionmentioning
confidence: 99%